Milciclib-mediated CDK2 inhibition to boost radiotherapy sensitivity in colorectal cancer - Ma, Junjie; Wu, Shanshan; Yang, Xinxin; Shen, Shuying; Zhu, Yiqian; Wang, Ruoqi; Xu, Wei; Li, Yue; Zhu, Haixin; Yan, Youyou; Lin, Nengming; Zhang, Bo (Frontiers in Pharmacology, 2025)
BackgroundColorectal cancer (CRC) ranks as the third most common cancer globally. Neoadjuvant radiotherapy is the standard treatment for locally advanced rectal cancer; however, primary or acquired resistance often leads to treatment failure. Identifying new targets to overcome radiotherapy resistance in CRC is crucial for improving patient outcomes.MethodsTo evaluate the antitumor effects of Milciclib in CRC cells, we conducted assays measuring cell viability, cell cycle progression, and apoptosis in HCT116 and RKO cell lines following Milciclib treatment. Additionally, CRC cells were treated with a combination of Milciclib and irradiation to determine whether Milciclib could enhance their radiosensitivity. The efficacy of Milciclib was also assessed in radiation-resistant CRC cells.ResultsThe results of cytotoxicity and proliferation assays indicated that the IC50 values of Milciclib for human colorectal cancer cell lines HCT-116 and RKO, based on cell viability measurements, were 0.275 μM and 0.403 μM, respectively. Milciclib induced a dose-dependent reduction in the proportion of CRC cells in the G2/M phase and promoted apoptosis. When combined with irradiation, Milciclib led to a 20% increase in the proportion of cells in the G1 phase and a 10% decrease in the G2 phase, suggesting an alteration in cell cycle distribution. Additionally, Milciclib impaired DNA damage repair by inhibiting Rad51, thereby enhancing radiation sensitivity. In radiation-resistant CRC cells, the combination of Milciclib and irradiation demonstrated increased efficacy, with a sensitizer enhancement ratio (SER) above 1, indicating a potential radiosensitizing effect.ConclusionMilciclib exhibits antitumor activity in CRC cells as a monotherapy and enhances the effectiveness of radiotherapy when used in combination. It disrupts the G2/M checkpoint and impairs DNA repair mechanisms. These findings suggest that Milciclib has the potential to be an effective therapeutic agent for CRC.